OPTIMALISASI FUEL TANKERING UNTUK SELURUH RUTE PENERBANGAN PT. SRIWIJAYA AIR DARI BANDAR UDARA SOEKARNO HATTA - Tyas Adimukti El Ridho Purba; Ika Endarwijaya; Amri Asmawan (Politeknik Penerbangan Indonesia Curug, 2017)
PT. Sriwijaya Air is one of the airlines operating in Indonesia. As an airline company, PT. Sriwijaya Air implement strategies in order to gain profit and reduce operational costs as small as possible. One of the strategies applied to reduce operational costs is by doing fuel tankering. In fact, the fuel tankering strategy implemented by PT. Sriwijaya Air has not taken place optimally. Not optimal because of the absence of reference on fuel tankering so that PIC (Pilot In Command) did not add fuel to make operational cost savings. Therefore, the need for the existence of fuel tankering calculation so that flight dispatcher has a reference in doing fuel tankering. It is expected that with the the reference of fuel tankering, the fuel tankering strategy applied by PT. Sriwijaya Air takes place optimally